The road to incorporating Scottish pelagic industry data in science for stock assessments - Mackinson, Steven; Brigden, Katie; Craig, Jessica; Clarke, Elizabeth D.; Angus, Chevonne; Pert, Campbell C. (Frontiers in Marine Science, 2023)
Fisheries data collection through industry-science partnerships have significant potential to support stock assessments and sustainable management, but few studies have described the steps taken en route to a successful partnership. This paper describes the development of the Scottish Pelagic Industry-Science Data Collection Programme; why and how it started, and what it has taken to develop a routine and consistent voluntary sampling regime of sufficient quality to become the main source of biological data on pelagic fish catches in Scotland. Using our experience, we emphasise the importance of establishing procedures that ensure the quality of methods and results, of working with institutions responsible for provision of national data, and of actively engaging with the International Council for the Exploration of the Sea (ICES) workshops and working groups on data quality, stock assessment and stakeholder engagement. The development of the programme has been, and remains to be, a mutual learning process which is reflected upon from our different institutional perspectives. The experience gained during this work has built knowledge useful for practitioners in other situations. Specifically, we identify five transferable design principles that we believe have been essential to success so far. Finally, we look at the steps ahead in our efforts toward continuous improvements.